The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 11th Nordic Conference on Human-Computer Interaction: Shaping Experiences, Shaping Society 2020
DOI: 10.1145/3419249.3420106
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Assessment of National Artificial Intelligence Policies: Perspectives from the Nordics and Beyond

Abstract: Echoing the evolving interest and impact of artificial intelligence on society, governments are increasingly looking for ways to strategically position themselves as both innovators and regulators in this new domain. One of the most explicit and accessible ways in which governments outline these plans is through national strategy and policy documents. We follow a systematic search strategy to identify national AI policy documents across twenty-five countries. Through an analysis of these documents, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The growing use of AI across a range of application domains has led to an increased focus on usable [9,39], fair [49,53], and transparent [4] systems within the HCI community as well as the wider public debate [33,50]. The successful uptake and deployment of these algorithmic systems does, however, rely on the incorporation of stakeholders' knowledge and feedback [62].…”
Section: Discussionmentioning
confidence: 99%
“…The growing use of AI across a range of application domains has led to an increased focus on usable [9,39], fair [49,53], and transparent [4] systems within the HCI community as well as the wider public debate [33,50]. The successful uptake and deployment of these algorithmic systems does, however, rely on the incorporation of stakeholders' knowledge and feedback [62].…”
Section: Discussionmentioning
confidence: 99%
“…Technological developments have led to an increase in the deployment of artifcial intelligence (AI) based decision-support solutions. Having moved beyond theoretical solutions or theories, such systems now have a profound efect on both individuals and society at large [25,57]. The use of AI spans across a variety of application domains, including high-impact areas such as loan approval [16,36], policing and law enforcement [29,31], and hiring processes [14,46].…”
Section: Introductionmentioning
confidence: 99%
“…Our study was limited to American crowdworkers, and prior work shows that perceptions towards e.g. AI behaviour and fairness difer signifcantly between geographical and cultural clusters[3,57].…”
mentioning
confidence: 99%
“…Buxmann and Schmidt [6] Labor market BMBF [57] Labor market Frey and Osborne [58] Labor market Grace et al [59] Labor market PWC [53] Labor market Economic production factor Begleitforschung PAiCE [54] Economic production Factor Nature [55] Economic production factor LBBW Research [56] Economic production factor Nankervis et al [37] Production factor Hartmann et al [60] Production factor Ansari [16] Vocational training concepts Ansari and Seidenberg [17] Vocational training concepts Feigh et al [26] Vocational training concepts Deutscher Bundestag [41] Legislation and politics Deutsche Bundesregierung [42] Legislation and politics Cath et al [43] Legislation and politics Singh [45] Legislation and politics van Berkel et al [44] Legislation and politics OECD [46] Legislation and politics Clarke [48] Legislation and politics Steels and López de Mantaras [51] Legislation and politics Park [47] Legislation O'Sullivan and Thierer [52] Politics van Nuenen et al [49] Discrimination Santow [50] Discrimination…”
mentioning
confidence: 99%
“…The study by van Berkel et al compared the national policy documents on AI of 25 countries. It was shown that the following topics occupy the world[44]:…”
mentioning
confidence: 99%